Māori resource management innovations - Bargh, Maria (Routledge Handbook of Critical Indigenous Studies, 2020)
The historical context of colonial legacies and capitalist policies are shaping responses to climate change but so too are non-capitalist and alternative-capitalist practices. Indigenous peoples’ world-views are commonly argued to align with non-capitalist approaches and often said to be the answer to climate change. However, Indigenous peoples are never only ‘ecological natives’ ‘living at one with nature’ but have multiple roles and identities in the political economy. Indigenous world-views could be used in ways to support capitalist practices and policies (which many argue have caused climate change) or to support alternative-capitalist practices (which others argue promote harmonious relationships between humans and the planet).
Keywords: capitalism; climate change; environment